O tratamento da variação linguística nos livros didáticos de Língua Portuguesa - Oliveira, Flávia Freitas de (2018)
The present work was motivated to investigate the treatment of linguistic variation in the textbooks of Portuguese Language of the High School approved by Public Announcement PNLD 2015 (Public Notice 01/2013), by the Ministry of Education (MEC).The central point is to verify and analyze how the teaching material presents proposals for activities of linguistic variation, highlighting the sociolinguistic aspects such as diachronic, diatopical, social, oral, written and diaphasic variations present in the main texts language. The theoretical foundations of this thesis go through the assumptions of Sociolinguistics, mainly the Labov Variationist theory, which also contributed to the theoretical-methodological foundation of our research, highlighting Labov ([1972] 2008), Tarallo (2007), Guy and Zilles 2007) and Ilari and Basso (2014). Besides the discussion about "linguistic norm" with contributions and conceptions of many authors of which we highlight Gnerre (1991), Padley (2001), Faraco (2008) and Lucchesi (2002, 2015), since the subject has an extensive debate in the Academy. And for this research, we do not explore the conception of discursive genres, but we adopt the definitions given by Bakhtin (2003), as well as the interpretation of these definitions by Fiorin (2016), besides the contributions on genres groupings by Dolz and Schneuwly (2004). The linguistic sample is formed from the activities on variation phenomena in the main texts, identified as discursive genres of the groupings in order of narrating and reporting, according to Dolz and Schneuwly (2004). Thus, we verified 1206 discursive genres, of which 497 are grouped in the orders of narrating and reporting and only 292 occurrences have phenomena variation in the style of the genre. After verifying the 292 occurrences, we selected only 57 occurrences that are followed by activities with variation treatment proposition. Thus, the corpus of the research is constituted by 57 discursive genres in order of narrating and reporting, followed by proposition of activities on linguistic variation of the text under analysis. The main goal of the thesis is to investigate how the different Portuguese Textbooks (LDP) deal with the theme of "linguistic variation" and, consequently, approach the idea of "standard norm" and "cultured norm", in order to contribute the discussion of the implementation of teaching policies from mother tongue to high school, such as the growing discussion about the existence of a "pedagogy of variation." After the investigation, we tabulated the data of treatment of linguistic variation in the LDP, presenting the activities that deal with aspects such as modality, registry, types of variation, standard norm, cultured norm, linguistic prejudice, sociolinguistic plurality, and the right and wrong culture reinforcement. The result corroborates in order to supplement the sociolinguistic data mapping of Brazilian Portuguese (PB), as well as to indicate what should be inserted and modified in the LDP, in order to contribute to the formation of the students' linguistic competence and which has been named by the pedagogy of variation.